Minimum Quantity Lubricant Flow Analysis In End Milling Processes: A Computational Fluid Dynamics Approach - Najiha, M. S.; M. M., Rahman; M., Kamal; A. R., Yusoff; K., Kadirgama (Faculty Mechanical Engineering, UMP, 2012)
This paper presents a two-dimensional steady-state incompressible analysis for the minimum quantity of lubricant flow in milling operations using a computational fluid dynamics (CFD) approach. The analysis of flow and heat transfer in a four-teeth milling cutter operation was undertaken. The domain of the rotating cutter along with the spray nozzle is defined. Operating cutting and boundary conditions are taken from the literature. A steady-state, pressure-based, planar analysis was performed with a viscous, realizable k-ε model. A mixture of oils and air were sprayed on the tool, which is considered to be rotating and is at a temperature near the melting temperature of the workpiece. Flow fields are obtained from the study. The vector plot of the flow field shows that the flow is not evenly distributed over the cutter surface, as well as the uneven distribution of the lubricant in the direction of the cutter rotation. It can be seen that the cutting fluid has not completely penetrated the tool edges. The turbulence created by the cutter rotation in the proximity of the tool throws oil drops out of the cutting zone. The nozzle position in relation to the feed direction is very important in order to obtain the optimum effect of the MQL flow.